2020
DOI: 10.3390/microorganisms8030430
|View full text |Cite
|
Sign up to set email alerts
|

Optimised Production and Extraction of Astaxanthin from the Yeast Xanthophyllomyces dendrorhous

Abstract: Currently, astaxanthin demand is fulfilled by chemical synthesis using petroleum-based feedstocks. As such, alternative pathways of natural astaxanthin production attracts much research interest. This study aimed at optimising bioreactor operation parameters for astaxanthin production and evaluating strategies for its subsequent extraction. The effect of pH and agitation was evident, as a significant reduction in both biomass and astaxanthin production was observed when the culture pH was not controlled and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 44 publications
0
29
0
Order By: Relevance
“…A combination of various types of enzymes, instead of just one type, acts simultaneously and leads to a more effective N-ASX release. It has been reported that the presence of β-1,3-glucanase, protease, cellulose, and pectinase gives high cell disruption and high N-ASX extraction yields in H. pluvialis and P. rhodozyma (Harith et al, 2020;Ye et al, 2020).…”
Section: Mechanical and Nonmechanical Cell Disruption Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A combination of various types of enzymes, instead of just one type, acts simultaneously and leads to a more effective N-ASX release. It has been reported that the presence of β-1,3-glucanase, protease, cellulose, and pectinase gives high cell disruption and high N-ASX extraction yields in H. pluvialis and P. rhodozyma (Harith et al, 2020;Ye et al, 2020).…”
Section: Mechanical and Nonmechanical Cell Disruption Methodsmentioning
confidence: 99%
“…Although molecule degradation occurred at 80°C, the highest purity of 34% was found at this temperature at 440 bars, 80 min, without cosolvent. The use of SC-CO 2 was recently reported in P. rhodozyma by Harith et al (2020). The authors studied the effect of the temperature, pressure, and ethanol concentration as a cosolvent in enzymatic pretreated cells and found that both pressure and cosolvent concentration significantly influenced N-ASX extraction.…”
Section: Nonconventional Extraction Methodsmentioning
confidence: 99%
“…Natural astaxanthin is extracted from synthesizing organisms and microorganisms that are cultured or collected for this purpose or extracted from by-products of the fish industry (mainly from crustaceans). Some organisms that synthesize astaxanthin are the following: microalgae ( Haematococcus pluvialis , Chlamydomonas nivalis [ 7 ], Chlorella zofingiensis [ 8 ], Neochloris wimmeri [ 9 ], Scenedesmus acutus [ 10 ]); bacteria ( Agrohacterium aurantiacum [ 11 ], Brevundimonas scallop [ 12 ], Paracoccus carotinifaciens [ 13 ]); yeasts ( Xanthophyllomyces dendrorhous [ 14 ]); Protista ( Aurantiochytrium [ 15 ]; Thraustochytrium [ 16 ]) and plants ( Adonis annua [ 17 ], Adonis aestivalis [ 18 ]). Since 1990, astaxanthin is synthetically produced and nowadays it is produced on a large scale, this being the most abundant method of production found in the world market (95% of the total) because of the lower cost of production (approximately 1000 dollars/kg) when compared with natural astaxanthin [ 5 , 19 ].…”
Section: Astaxanthin: a Valuable Marine Resourcementioning
confidence: 99%
“…Supercritical carbon dioxide extraction has also been used to obtain astaxanthin [ 40 , 41 ]. The use of high pressure to improve the efficacy of the solvent during the extraction of astaxanthin has also been proposed [ 42 ], as well as ultrasound [ 43 ], microwave [ 44 ], magnetic-field-assisted extraction [ 45 ], pulsed electric field [ 46 ], microbial fermentation [ 14 ], and the use of enzymes [ 47 ].…”
Section: Astaxanthin: a Valuable Marine Resourcementioning
confidence: 99%
“…Xanthophyllomyces dendrorhous represent a promising choice for astaxanthin production because of the high astaxanthin yields and productivities that have been associated with this yeast (Tropea et al 2013;Gervasi et al 2020;Harith et al 2020). The cultivation of this microorganisms, through a fed-batch mode, that allow the addition of nutrients to the reactor during fermentation in order to maintain the concentration of the substrate below its inhibitory levels, have been used in this study.…”
Section: Introductionmentioning
confidence: 99%